OVERLAPPING MARITIME SECURITY: CHALLENGES AND OPPORTUNITIES FOR INVESTMENT IN INDONESIA'S EXCLUSIVE ECONOMIC ZONE: OVERLAPPING MARITIME SECURITY: CHALLENGES AND OPPORTUNITIES FOR INVESTMENT IN INDONESIA'S EXCLUSIVE ECONOMIC ZONE - Dwikora, Buyung; Hasibuan, Fauzie Yusuf; Rattanapun, Supot (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2024)
This study examines the state's responsibility in ensuring investment security within Indonesia's Exclusive Economic Zone (EEZ), analyzing the roles of law enforcement officials and security institutions. The research highlights the importance of a stable regulatory framework and effective maritime security measures to foster a conducive environment for both domestic and foreign investors. It identifies the challenges posed by overlapping authorities among various agencies, which can lead to inconsistent law enforcement and uncertainties that discourage investment. By reviewing relevant laws, regulations, and institutional frameworks, the study emphasizes the need for improved coordination among maritime security agencies, enhanced surveillance technologies, and a comprehensive legal framework. The findings suggest that addressing these challenges will not only protect national interests but also promote investor confidence, unlocking the economic potential of Indonesia's EEZ in sectors such as fisheries, energy, and maritime transportation. Ultimately, this research contributes to a deeper understanding of the intersection between maritime security and investment opportunities, providing valuable insights for policymakers and stakeholders involved in Indonesia's maritime governance.